(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Bao TQ, Ha NT, Nguyet BTM, Hoan VM, Viet LH, Hung DV. 2021. Aboveground biomass and carbon stock of Rhizophora apiculata forest in Ca Mau, Vietnam. Biodiversitas 23: 403-414. Despite the small proportion of mangrove forests globally, they contribute significantly in carbon storage. Yet, biomass and carbon stock in mangrove forests might vary depending on various factors including the dominant species that occurred. This study was conducted to determine the biomass and carbon stock of a mangrove forest dominated by Rhizophora apiculata Blume in Ca Mau, Vietnam. Data were collected from 56 representative sample plots (50m x 50m), and 46 sample trees with different age classes and diameter sizes were cut down to measure the fresh biomass. The dry biomass and carbon content were analyzed in the laboratory. The average aboveground biomass and carbon stock of the individual tree and the R. apiculata forest at different diameter sizes had a significant difference and were mostly found in the stem (74.5%-79.5%). The conversion factor from fresh biomass to dry biomass was 0.56; the conversion factor from dry biomass to carbon was 0.46. The total biomass of the individual trees had a close relationship with two variables diameter at breast height (DBH) and height (Hvn) in the form of the logarithmic function: ln(Wtk) = -1,86412 - 1,95419*ln(Hvn) + 2,26798*ln(DBH*Hvn). The total biomass and carbon stock of the entire forest stand increased in accordance with the diameter size and age classes. The R. apiculata stand had a density of 1,040-15,800 trees/ha and a timber volume of 27.2 to 365.6 m3/ha. The average biomass of the R. apiculata stand was 191.1 tons/ha with a range from 49.6 to 357.4 tons/ha. The carbon stock in forest biomass ranged from 23.8 to 188.7 tons C/ha, with an average of 117.4 tons C/ha. The forest’s CO2 absorption ranged from 60.0 to 691.7 tons CO2/ha, with an average of 415.9 tons/ha. The carbon stocks of trees of age class I to age class VI were 41.6 tons C/ha, 79.4 tons C/ha, 101.4 tons C/ha, 132.9 tons C/ha, 154.0 tons C/ha, and 167.4 tons C/ha, respectively.